Sports League Expansion and Economic Efficiency: Monopoly Can Enhance Consumer Welfare - Lawrence Kahn (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper studies optimal sport league size. League expansion lowers average player quality, reducing fans' utility in inframarginal locations, while fan utility in new locations rises. Welfare analyses of such expansions must compare these two effects. Using a model where fan demand depends on average player quality and locality-specific factors, I find that under various pricing schemes, optimal league size is smaller than under free entry: the marginal team ignores its effects on inframarginal fans' utility. In some cases, the monopoly outcome is optimal, while in others the optimum league size is between the competitive and monopoly solutions.
Keywords: L10; L40; 330